Comparing the Knee Joint Kinematic Parameters of Female Athletes During Sidestep Cutting Task Before and After Fatigue in Predictable and Unpredictable Settings - Elham Hosseini; Abdolhamid Daneshjoo; Mansour Sahebozamani (Islamic Azad University, Hamedan Branch, 2019)
Objective: Anterior cruciate ligament injury is often non-traumatic and occurs in landing and cutting following an incorrect knee joint alignment. The present study aimed to compare the knee joint kinematic parameters of adolescent female athletes during sidestep cutting maneuver before and after fatigue in predictable and unpredictable settings. Methods: This is a quasi-experimental study conducted in the summer 2019. The study population consists of all adolescent female athletes in Kerman, Iran. Of these, 49 athletes were selected using purposive and convenience sampling methods. Each subject first ran a distance (10 m) and then made a vertical jump towards the ball at the specified location. Afterwards, she ran to the cutting location (a 3-m distance) and performed sidestep cutting at the specified angle, predictably or unpredictably, before and after fatigue. Kinematic data were recorded at a sampling rate of 200 HZ, and then analyzed in MATLAB and SPSS software using mixed repeated measures ANOVA at the significant level of P<0.05. Results: Statistical analysis results showed that sidestep cutting maneuver after fatigue, despite a significant decrease in knee flexion (P=0.001), significantly increased the knee valgus (P=0.001) and tibia rotation (P=0.001) angles. Conclusion: There is an increased risk of injury due to changes in kinematic parameters caused by fatigue and unpredictable cutting maneuvers.